Analisis Regresi Linear Berganda untuk Perhitungan Pendapatan Asli Daerah Jawa Barat - Panjaitan, Amanda Ardita; Wisna, Nelsi; Fahrudin, Tora (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Regional Original Revenue is a receipt of funds obtained from the management of the original potential of the region in accordance with the laws and regulations. Motor Vehicle Tax is one of the main contributors to Local Owned Revenue (PAD) which is used to finance regional development and expenditures. This study aims to evaluate the impact of Motor Vehicle Tax, Motor Vehicle Title Transfer Fee, and Regional Retribution on Regional Original Revenue in West Java Province in the period 2018-2023. The research method used is quantitative using secondary data collected through documentation. Hypothesis analysis was conducted using multiple linear regression with the help of SPSS software, including the F test, t test, and simultaneous and partial determination analysis. The research findings show that Motor Vehicle Tax (PKB), Motor Vehicle Title Transfer Fee (BBNKB), and Regional Retribution significantly affect West Java's Original Revenue.